The relationship between students' science process skills and awareness in environmental issues using outdoor learning - Luluk Hamidah; I Gusti Putu Suryadarma (Universitas Ahmad Dahlan, 2021)
Outdoor Learning has been recognized as a learning strategy to be learned and applied in enhancing students science process skills and awareness. However, the problem of waste management is the biggest challenge because it has not been realized in vocational high schools. Students science process skills and awareness are needed to develop the student's potential insight, attitude, and employability skills. This study aimed to analyze the relationship between science process skills and awareness using the outdoor learning process. The research type is a quasi-experiment. Samples were obtained from students and used purposive sampling. The essay instrument consists of 10 items developed of science process skills. Awareness is measured using a test questionnaire consisting of 19 items. The collected data were analyzed through prerequisite, Independent Sample test T-Test, Gain Score, multivariate analysis of Variance (MANOVA), and Pearson correlation tests. The result showed that the outdoor learning application enables to increase between science process skills and awareness aspects. The test results of each class Showed that the difference significant. It means there was a positive relation, shown by a significant score of 0.042 with 0.05 standard. The results of the analysis show the Pearson correlation value of the two variables is 0.291, it can be interpreted that the relationship between the two variables has a low relationship, but the average response value of awareness after learning increased compared before learning in the two treatment groups.